Efeitos da poluição pontual e difusa na qualidade de água em reservatórios do semiárido - Silva, Paulo Roberto Nunes da (2015)
The construction of reservoirs has become a palliative to remedy or alleviate water shortages primarily of semi-arid regions. However, these artificial environments are constantly subjected to human pressures, considerably reducing its quality for human consumption. Thus, the aim of this study is to identify and measure the point and diffuse sources of pollution and its influence on water quality of two reservoirs located in the course of the river Paraíba / PB Basin. The study was conducted in Epitácio Pessoa and Argemiro de Figueiredo reservoir, located in the city of Epitácio Pessoa and Itatuba - PB, respectively. They were delimited 20 sampling sites for each reservoir. Samples of water and sediment in coastal areas were collected, besides the application of characterization of physical habitats protocols in May 2014. In order to measure the phosphorus input through the point and diffuse sources into the water, it used one proposed mathematical model by Vollenweider (1976). The results verified that the surroundings are relatively impacted and may be susceptible to discharges of nutrients and contaminants. The water quality of the reservoirs showed some environmental and microbiological variables changed by the suggested by the classification standards of water bodies and environmental guidelines for its framework of CONAMA (2005) for human drinking water. The Epitácio Pessoa reservoir, said, from protocols such as greater degree of impact, by presenting the largest metric of anthropogenic disturbance, but was seen as less polluted compared to Argemiro de Figueiredo. According to the results obtained by mathematical modeling, pollutants that reach the Pessoa waters are diffuse and point source in Argemiro de Figueiredo.